2004
DOI: 10.1086/382905
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Neighboring Galaxies

Abstract: We present an all-sky catalog of 451 nearby galaxies, each having an individual distance estimate D P 10 Mpc or a radial velocity V LG < 550 km s À1 . The catalog contains data on basic optical and H i properties of the galaxies, in particular, their diameters, absolute magnitudes, morphological types, circumnuclear region types, optical and H i surface brightnesses, rotational velocities, and indicative mass-to-luminosity and H i massto-luminosity ratios, as well as a so-called tidal index, which quantifies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,016
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 750 publications
(1,051 citation statements)
references
References 154 publications
25
1,016
1
3
Order By: Relevance
“…In order to estimate this, we use the catalog of nearby galaxies given by Karachentsev et al (2004). This catalog is nearly complete out to a distance of 10 Mpc and it contains a total of 431 galaxies with known mass for 313 galaxies.…”
Section: Estimation Of the External Fifth Forcementioning
confidence: 99%
“…In order to estimate this, we use the catalog of nearby galaxies given by Karachentsev et al (2004). This catalog is nearly complete out to a distance of 10 Mpc and it contains a total of 431 galaxies with known mass for 313 galaxies.…”
Section: Estimation Of the External Fifth Forcementioning
confidence: 99%
“…Hence the question remained how these two types of dwarf galaxies are formed. We have incorporated the above idea in the present model by assuming that the formation of dEs or dIrrs depends on a random variable Θ (Karachentsev et al 2004). We indeed found in an earlier paper (Chattopadhyay et al 2010) that dE galaxy formation is preferred when Θ > 0 and that of dIrrs when Θ < 0.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper (Chattopadhyay et al 2010) we classified dwarf galaxies on the basis of several parameters and found two groups, one dominated by dIrrs and the other by dEs, and for these two groups the average value of Θ was negative and positive, respectively. The observed values of Θ, taken from Karachentsev et al(2004), are given in Table 1 along with galaxy names and morphological indices T.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations